Create your own employee handbook : a legal & practical guide for employers - Guerin, Lisa, 1964-; DelPo, Amy, 1967- (Berkeley, California : Nolo, 2015)
Make - or update - your employee handbook today! Clear employee policies help you run a productive workplace and avoid legal problems. Create Your Own Employee Handbook provides everything managers or HR professionals need to create a reader-friendly guide, or update an existing handbook--all in plain English. Find up-to-date legal information, practical suggestions and best practices on: wages and hours at-will employment time off discrimination and harassment complaints and investigations health and safety drugs and alcohol workplace privacy email, personal blogs and Internet use You'll get the lowdown on the legal and practical considerations that apply to each topic in your state, plus sample policies that you can use as-is or tailor to meet your needs. You can even cut and paste the language you need to complete your own handbook instantly. The 7th edition covers recent updates to the law, including social media use, health care reform, rules for tipped employees and much more!
Handbook introduction -- At-will protections -- Hiring -- New employee information -- Employee classifications -- Hours -- Pay policies -- Employee benefits -- Use of company property -- Leave and time off -- Performance -- Workplace behavior -- Health and safety -- Employee privacy -- Computers, email, and the internet -- Employee records -- Drugs and alcohol -- Trade secrets and conflicts of interest -- Discrimination and harassment -- Complaint policies -- Ending employment.
Includes bibliographical references and index.
Keywords: Employee orientation; Employees -- Training of; Employee rights; Employee rules; Law for laypersons